2021
DOI: 10.3389/fcell.2021.727183
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pyroptosis-Associated Long Non-coding RNA Signature Predicts Prognosis and Tumor Immune Microenvironment of Patients With Breast Cancer

Abstract: Background: Pyroptosis, a kind of programmed cell death characterized by the rupture of cell membranes and the release of inflammatory substances, plays an important role in the occurrence and development of cancer. However, few studies focus on the pyroptosis-associated long non-coding RNAs (lncRNAs) in breast cancer (BC). The prognostic value of pyroptosis-associated lncRNAs and their relationship with tumor microenvironment (TME) in BC remain unclear. The purpose of this study was to explore the prognostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…Due to the rapid development of bioinformatics in recent years, sifting pyroptosis-related mRNA or lncRNA as prognostic signatures has become a reality, which is helpful to understand their role in the occurrence, development, and prognosis of carcinoma and provide new ideas for clinical prevention and treatment [ 10 , 11 ]. In the current study, we downloaded and analysed a dataset of lncRNA expression in bladder cancer from The Cancer Genome Atlas (TCGA).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the rapid development of bioinformatics in recent years, sifting pyroptosis-related mRNA or lncRNA as prognostic signatures has become a reality, which is helpful to understand their role in the occurrence, development, and prognosis of carcinoma and provide new ideas for clinical prevention and treatment [ 10 , 11 ]. In the current study, we downloaded and analysed a dataset of lncRNA expression in bladder cancer from The Cancer Genome Atlas (TCGA).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the activation of pyroptosis tends to be accompanied by a severe inflammatory response that may affect the TIME; therefore, like other forms of PCDs such as apoptosis, autophagy, and ferroptosis, pyroptosis has become one of the hot topics in current cancer research ( Hsu et al, 2021 ). Recent studies have investigated the prognostic significance of pyroptosis and its connections with the TIME ( Ping et al, 2021 ; Sun et al, 2021 ; Wu et al, 2021 ; Ye et al, 2021 ). However, whether pyroptosis is correlated with the prognosis or specific microenvironment of patients with PAAD or not remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has also confirmed the pivotal role of PR in the anti-tumor function of NK cells (Zhang et al, 2020b). Ping, Liqin and Lv W et al also demonstrated that PR-associated lncRNAs serve a prognostic role in breast cancer as well as its correlation with TME (Lv et al, 2021;Ping et al, 2021). Therefore, PR plays an important role in tumor development and the antitumor process (Wu et al, 2021); however, its specific function in BC remains to be further elucidated.…”
Section: Introductionmentioning
confidence: 89%